2021
DOI: 10.1002/anie.202104843
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo‐like π‐Nanotubes with Tunable Helicity and Circularly Polarized Luminescence

Abstract: We report the fabrication of an exotic bamboo-like p-nanotube via the hierarchical self-assembly of ad ipeptidesubstituted naphthalenediimide gelator with tunable helicity and circularly polarized luminescence (CPL). It was found that in the presence of trifluoroacetic acid (TFA) the gelator molecules self-assembled into ab amboo-like p-nanotube, which is composed of truncated nanocones and CPL active. When defining the diameter ratio of the lower to upper edge of each nanocone as ap arameter to express the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 81 publications
(2 reference statements)
0
29
0
Order By: Relevance
“…With the rapid development of supramolecular chemistry in the past several decades, chiral supramolecular self-assemblies and co-assemblies have been assigned to be one of the most suitable and promising CPL-active materials [70][71][72][73]. These chiral self-assemblies and co-assemblies with designable microstructures could provide a powerful approach to precisely regulate the arrangement of building blocks and promote the amplified CPL signals during assembly process via noncovalent interactions (π-π stacking, hydrogen bonds, hydrophobic interactions, van der Waals interactions, and hostguest interactions) [10,14,43,[74][75][76][77][78][79]. Several advantages of the supramolecular assemblies are provided.…”
Section: Cpl-active Supramolecular Assembliesmentioning
confidence: 99%
“…With the rapid development of supramolecular chemistry in the past several decades, chiral supramolecular self-assemblies and co-assemblies have been assigned to be one of the most suitable and promising CPL-active materials [70][71][72][73]. These chiral self-assemblies and co-assemblies with designable microstructures could provide a powerful approach to precisely regulate the arrangement of building blocks and promote the amplified CPL signals during assembly process via noncovalent interactions (π-π stacking, hydrogen bonds, hydrophobic interactions, van der Waals interactions, and hostguest interactions) [10,14,43,[74][75][76][77][78][79]. Several advantages of the supramolecular assemblies are provided.…”
Section: Cpl-active Supramolecular Assembliesmentioning
confidence: 99%
“…For initial D-PhgC16 self-assemblies, the bands at 3306 cm -1 and 1730 cm -1 were attributable to the N-H and C=O (from carboxyl groups) stretching vibrations, respectively. 33 The amide I band at 1651 cm -1 and amide II band at 1537 cm -1 were also observed. 33 These bands demonstrated the formation of favorable hydrogen bond networks between the amide and carboxyl groups of D-PhgC16 molecules.…”
Section: Resultsmentioning
confidence: 88%
“…33 The amide I band at 1651 cm -1 and amide II band at 1537 cm -1 were also observed. 33 These bands demonstrated the formation of favorable hydrogen bond networks between the amide and carboxyl groups of D-PhgC16 molecules. 33 In the case of D-PhgC16/MPD, the band at 1730 cm -1 was significantly reduced and a new peak at 1696 cm -1 emerged, which might owing to the electrostatic interactions between the amino units of MPD and the carboxyl groups of D-PhgC16.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Chirality induction by the assemblies of nonchiral building blocks on the chiral templates has been widely studied in recent decades especially for various organic self-assemblies, , organic and inorganic hybrid self-organization such as plasmonic gold nanoparticles and QDs. While the self-organization with organic molecules suffers limited organization stability with external parameters such as temperature, solvent, salinity, or pH, , the alternative inorganic chiral nanosystem is still at an emerging point to get stable dense and well-packed self-organization system. Recently, we reported that gold nanoparticles electrostatically or covalently bonded on the surface of nanometric inorganic silica helical ribbons show plasmonic induced CD mirror images in suspension, , the sign of which can simply be controlled by the handedness of the silica helices.…”
mentioning
confidence: 99%